The Peningkatan Kualitas Human Capital Melalui Pembelajaran Kewirausahaan di SMK Negeri 1 Driyorejo - Ucik Rachmawati (Jurnal Bintang Pendidikan Indonesia, 2023)
The researcher carried out this research because he wanted to examine how to improve the quality of human capital through entrepreneurship learning at SMKN 1 Driyorejo Gresik. In improving the quality of human capital, one of them is requiring an effective learning, namely by implementing this entrepreneurship. This research uses a qualitative approach that is descriptive and the type of research is a case study. Data collection techniques used by researchers are observing, interviewing and documenting. Meanwhile, data analysis is carried out using data condensation, data presentation, and data verification. In testing the validity of the data, researchers also used source triangulation and technique triangulation. The results of this study show that SMKN 1 Driyorejo Gresik has implemented entrepreneurship learning in creating superior quality human capital so that graduates become entrepreneurship, especially in grades eleven and twelfth. Not only that, SMKN 1 Driyorejo Gresik already has excellent products, namely Skandry Water and Skandry Hygenice. Therefore, it is hoped that all residents of SMKN 1 Driyorejo will apply the KISS method, namely Consolidation, Integration, Synergy and Synchronization so that school plans can be realized and implemented perfectly because they are supported by all school members.